Rancang Bangun Purwarupa Sistem Kendali Kecepatan Motor Dc Pada Speedboat Tenaga Surya - julsen kadri; Rusman; Wendhi Yuniarto (entries, 2026)
This study aims to design and test a 12 V DC motor speed control system for a solar-powered speedboat prototype using the Pulse Width Modulation (PWM) method. The system is controlled by an Arduino Uno with a full-bridge motor driver. Speed regulation is performed by varying the PWM duty cycle using two control methods: analog control with a potentiometer and digital control via Bluetooth communication. The system is also equipped with an ACS712 current sensor and a voltage divider circuit for overcurrent and overvoltage protection. Experimental results show that increasing the PWM duty cycle from 10% to 80% raises the motor voltage from 1.2 V to 10.2 V and the speed from 761.6 RPM to 7,664.4 RPM. The protection system is activated when the current exceeds 10 A